Propaganda strategies in Nazi and Russian cinematography - Bezhnar, Ganna (Ukrainian Cultural Studies, 2025)
Background. Despite the necessity of removing Russian imperialist culture from everyday life, its critical academic analysis from a Ukrainian perspective has never been more important than during the ongoing full-scale invasion. The article focuses on contemporary Russian cinematography as a representative component of the invader's media practices. The goal of the article is to identify the propagandistic frameworks employed in both Nazi and contemporary Russian cinematography.Methods. The study employs general scientific methods, including analytical, comparative, and generalization techniques.Results. The concept of "propaganda" today refers to an effective instrument of political influence on mass consciousness, actively employed by totalitarian regimes in the 20th century. Сinematography has been closely connected with propaganda due to its ability to convey ideological messages through visual imagery and emotional appeal. The propagandistic function of film is especially evident in Nazi Germany. This study focuses on Leni Riefenstahl's films as examples of the aestheticization of power, the construction of a leader cult, and the sacralization of political ideology. The article also examines the creation of the enemy image as a key propaganda strategy. The article reveals how the glorification of war served as a mechanism for shaping collective consciousness to perceive violence as both necessary and justified. It is noted that cinema in the Third Reich not only documented events but also constructed emotionally charged visual rhetoric aimed at elevating the regime. A significant part of the research is dedicated to the analysis of Russian cinematography, which inherits the propaganda models of the Soviet era. In contemporary films, the image of the Second World War is sacralized, Soviet soldiers are heroized, and war is portrayed as a noble and morally justified act. Special attention is paid to anti-Ukrainian rhetoric in Russian films.Conclusions. There is a conceptual continuity between the propagandistic strategies of Nazi Germany's cinematography and those employed by the contemporary Russian film industry. These strategies – enemy image construction, aestheticization of power, leader cult promotion, and glorification of war – remain effective tools of ideological influence on both mass consciousness and political discourse.
Keywords: propaganda; cinema; war; legitimation of violence; leader cult; dehumanization; aesthetization of power